Excitability Changes in Occipital Cortex After Continuous Theta-Burst Stimulation - Aghamirzayeva, Khayala; Temuçin, Çağrı Mesut; Yıldız, Fatma Gökçem (Noro-Psikiyatri Arsivi, 2024)
Modulation of visual cortical structures by repetitive transcranial magnetic stimulation is rarely observed in literature. In this study; the researchers aimed to investigate the neurophysiological alterations by using continuous theta burst stimulation (cTBS) protocol over the occipital cortex in healthy subjects. Twenty-five (15 female, 10 male) (mean age 29.84±4.7 years) healthy individuals were included in sham and real cTBS occipital stimulation sessions. Before and after each session, neurophysiological studies including phosphene threshold and visual evoked potential (VEP) responses were recorded. The P100 latency values and maximum amplitude values between N75-P100 peaks of 100 responses of 1000 uninterrupted continuous visual stimuli were measured. The VEP habituation and phosphene thresholds were compared in sham and real cTBS sessions. The phosphene threshold values increased to statistically significant levels after the real cTBS session. Visual evoked potential habituation was observed in both sham and real cTBS sessions in individuals without significant differences. Also, no difference between the P100 latencies and N75-P100 amplitude values in the sham and real cTBS sessions was observed. Phosphene threshold measurements demonstrated the modulation of the occipital cortex excitability via cTBS in healthy subjects.